From hazard identification to risk assessment: The role of the prevention technician in the carcinogenic risk assessment for formaldehyde - Pattavina, Fabio; Wachocka, Malgorzata; Tuti, Federica; Boninti, Federica; Santi, Riccardo; Grossi, Roberta; Laurenti, Patrizia (Frontiers in Public Health, 2023)
The Prevention Technician in the Environment and Workplaces (PTEW) is a health professionist who works in the identification, assessment and management of risk in living and working places. The PTEW implements specific corrective actions at reducing exposure level to chemicals such as Formaldehyde. The aim of this report is update the Formaldehyde Risk Assessment Document RAD. The risk assessment process was divided into three steps: 1) preliminary data collection, 2) on site visit to identify the use patterns and process, 3) application of the algorithm to calculate the exposure levels of health care workers.In addition, with the introduction of closed-circuit systems, 23 devices were evaluated in order to identify possible airborne dispersion of formaldehyde The algorithm was applied in 31 hospital units and the results c the staff in two levels of exposure for each hospital unit, health care workers were classified as "exposed" or "potentially exposed." Most HCWs are categorized as potentially exposed, only workers working in laboratories are considered to be exposed. The results showed that devices must be used properly according to the user manual, . To increase the level of worker safety, we have proposed to introduce the closed-circuit safe handling systems and keeping the duration and intensity of exposure at the lowest possible levels according to the "ALARA" principle. The task of the Italian PTEW is to achieve excellence in the levels of health and safety of patients and hospital workers by pursuing a shared mission: improving the quality of public health.